Dynamique forestière et pression urbaine dans le Parc national du Banco (Abidjan, Côte d’Ivoire) - Nakouma Sako; Gérard Beltrando; Koffi Lazare Atta; Hyppolite Dibi N’da; Télesphore Brou (VertigO)
Since 1960s, the Ivorian government care about his forest conservation. Thus, the Ivory Coast has set up a network of protected areas to conserve its forests and biodiversity. Located in Abidjan, the Banco National Park (PNB) and its periphery face a deeply environment changes in recent decades. This research aims to describe and analyze the various threats to urban pressure, including the risks of deforestation and pollution around and inside the PNB. To achieve these objectives, the analysis of the land cover and vegetation change help to understand the environmental dynamics of the Banco forest. The inventory and mapping of the types of risk and their impact on PNB enable to show the most vulnerable areas due to anthropogenic pressures and urbanization. The study of the types of human pressures in PNB is conducted through observations to detect spatial changes in recent years. The study also relies on an aerial photograph of 1955 and Spot satellite image taken in 1998. Aerial photography was acquired at the Centre of Cartography and Remote Sensing and the National Geographic Institute (IGN-Paris). The satellite image was obtained with the ISIS program of Spot Image. These data were used to map land cover in 1955 and 1998 and compare the evolution of the vegetation through a diachronic analysis.Indeed, in the year 1955, the land in the park and its periphery showed that the landscape was dominated by the forest despite the presence of a few urban space. The forest covered an area of 5462 ha while secondary forest covered an area of 9220 ha. These two types of forest represented nearly 90 % of the landscape of the study area. In 1998, 3450 ha of forest and 434 ha of forest plantations represente the vegetation of the PNB. Bordered by four towns, the Banco National Park suffers from the consequences of rapid urbanization. This rapid growth in the district of Abidjan has created many environmental problems, including the proliferation of shantytowns, inadequate facilities and transport infrastructure, sanitation and housing. The park is bordered to the north, east and south many poor neighborhoods without sanitation equipment. The PNB is to be the outlet for solid and liquid waste from households. Municipal storm water is discharged into the park. Multiple industrial units, informal activities and new residential areas bordering the park which is already facing since a decades to the creation of many facilities (creation of motorways, express roads, infrastructure and equipment necessary to meet demand of urban water, electricity etc..). In addition, many areas of PNB are subject to land claims, including the north-east and south of the park. These disputed areas are correlated with particular types of communities along the villages of Anonkoua Kouté Sagbé and north-Agban Attié and Agban-village southeast, and southwest Andokoi. In order to improve the protection of PNB and to enable his participation in economic development of people, its directors have established a policy of participatory management. This strategy involves local people in conservation. The association of local people in the community management of forest resources can empower them by involving them in monitoring missions, recovery and development. The development of the park through ecotourism, the development of alternative activities toward poachers and illegal loggers are among the many strategies implemented to save this threatened ecosystem. Ecotourism has become the most important policy of participatory management of public administrators of PNB.